SOSIALISASI TEKNIK BAURAN PEMASARAN PADA PRODUK USAHA MIKRO KECIL DAN MENENGAH (UMKM) DI KECAMATAN RAWAMERTA, KARAWANG - Asih, Anisa Mukti; Fahlevi, Rizal; Rahmawati, Rafika; -, Isfandayani; Widyananto, Arief (DEVOSI, 2021)
The role of Micro, Small and Medium Enterprises in increasing income and employment can certainly be considered large for Indonesia. MSME actors need to be given training related to delivering or disseminating knowledge information about the marketing mix for their products. The method used in this community service is in the form of socialization to the government of the Rawamerta sub-district and the surrounding community. The result was that 15 participants took part in the socialization activity to increase knowledge and information about the marketing mix for Micro, Small and Medium Enterprises products.